The ethics of fertility treatment for same-sex male couples: Considerations for a modern fertility clinic. (January 2020) - Mackenzie, Scott C.; Wickins-Drazilova, Dita; Wickins, Jeremy
Abstract: Social and legal equality for same-sex male couples continues to grow in many countries. Consequently, increasing numbers of same-sex male couples are seeking assisted reproductive technology to achieve parenthood. Fertility treatment for same-sex male couples is an undoubtedly complex issue and raises a variety of ethical concerns. Relevant considerations include ethical issues relating to the surrogate and a possible egg donor, the commissioning same-sex couple, the welfare of the child and the fertility clinic itself. This work analyses these arguments in the context of modern fertility services, providing reflection on the evidence present and what it means for clinicians today. Herein, we argue that fertility treatment for same-sex male couples via surrogacy agreements are acceptable, subject to considerations of each individual case, as in all assisted reproductive treatment. It is in the interest of open and equal access to health services that barriers to assisted reproductive technology for same-sex male couples should be minimised where possible.